Transforming language ideologies in the Styrias and in Prekmurje - Wiedner, Jakob (Studia Historica Slovenica, 2025)
The article examines how monolingual ideologies shape language policies and identities in the Slovenian-Austrian border region through a qualitative analysis of interviews. Rooted in ethno-linguistic nationalism, these ideologies continue to influence language policies, particularly through linguistic purism and a persistent "discourse of threat". Monolingual narratives often overlook historical multilingual realities and cross-border communities. Interview data show that younger generations are shifting toward linguistic pragmatism, embracing local dialects, English, and a European identity. Overall, while nationalistic discourses still linger, generational change and EU integration foster a more inclusive understanding of languages and identities in the region.
Keywords: avstrijska Štajerska; discursive practices; diskurzivna praksa; German language; jezikovni nacionalizem; linguistic capital; nemščina; obmejna območja; Prekmurje; qualitative analyses; Slovene language; slovenska Štajerska; slovenščina; sociolingvistika; Styria; vernacular nationalism